2019
DOI: 10.1088/1361-6595/ab0969
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of compact ECR plasma source for thruster applications

Abstract: The performance of a plasma thruster is assessed for efficient propulsion by analyzing the unique downstream characteristics of plasma produced by a Compact ECR Plasma Source (CEPS). For this, data presented in an earlier publication (Ganguli et al 2016 Plasma Sources Sci. Technol. 25 025026), wherein plasma produced in the CEPS is allowed to flow into a small stainless (SS) steel chamber, are revisited so as to throw new light on the nature of the plasma flowing out from the CEPS. It is shown that the normali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Once the plasma makes a transition to the two-electron population state, it remains in that state throughout, including the expansion chamber. In numerous studies on ECR plasma production [27][28][29][30][31] it is the latter state that is observed always, indicating that it is the more stable state. It is only in the present experiments that the state with single electron population characterized by warm bulk electrons and high plasma potentials could be observed since it was possible to access the ECR zone by probes.…”
Section: Axial and Radial Profilesmentioning
confidence: 97%
See 1 more Smart Citation
“…Once the plasma makes a transition to the two-electron population state, it remains in that state throughout, including the expansion chamber. In numerous studies on ECR plasma production [27][28][29][30][31] it is the latter state that is observed always, indicating that it is the more stable state. It is only in the present experiments that the state with single electron population characterized by warm bulk electrons and high plasma potentials could be observed since it was possible to access the ECR zone by probes.…”
Section: Axial and Radial Profilesmentioning
confidence: 97%
“…Some preliminary studies using these sources have also been undertaken. The CEPS has been used singly as a standalone source by attaching it to a small chamber [27,28]. Multiple CEPS (up to 12 in number) have also been used for lling a very large volume system [29,30] (∼1.7 m 3 ; dia ≈ 1 m) with high density, highly uniform plasma using very modest microwave power in each CEPS.…”
Section: Introductionmentioning
confidence: 99%
“…The importance and applicability of laser plasma interactions are well known and strongly pursued in the context of fusion [1,2], particle acceleration [3,4], etc. Microwaves are also being employed for many studies, such as the generation of plasma sources and diagnostics [5][6][7][8][9][10]. Its absorption leads to plasma heating [11], which is important in several contexts, such as tokamak [12,13], stellarator [14,15], particle * Authors to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In ECR, the magnetic field lines are parallel to the EM wave propagation direction, and electrons rotate in the same direction as the electric field of EM wave in a plane perpendicular to the direction of the external magnetic field. This technique is widely used for heating purpose in fusion plasmas [35][36][37], plasma thruster [38], etc. Another heating mechanism in a magnetized plasma is the mode conversion into an upperhybrid (UH) wave [39], which propagates perpendicular to the external magnetic field.…”
Section: Introductionmentioning
confidence: 99%